Investigating the Association Between Family Socioeconomic Profile and Diabetes Control in Children: A Cross‐Sectional Study From Sudan - Hiba Ali Elzaki Hajomer; Osama Ahmed Elkhidir; Rooa Mohammed; Suodad Elhassan; Aya Abdelrahim; Yousra Ibrahim Abdallah Mohammed (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aims Diabetes mellitus is the most common endocrine disease in childhood which significantly impacts quality of life, morbidity and mortality. This study aimed to investigate the socioeconomic background of children with diabetes and their families and to assess its association with diabetes control. Methods This cross‐sectional study was conducted in Khartoum State, Sudan, in 2018, at three outpatient diabetes clinics, using standardised questionnaires. We included 138 diabetic children (T1D and T2D) aged 2–18 years using systematic random sampling. Descriptive statistics, economic indicator and inferential statistics were applied using SPSS version 20. An HbA1C level of > 7.0% was set as the cut‐point for uncontrolled diabetes. A p‐value of < 0.05 was considered statistically significant. Results The mean age of the children was 11.1 (3.64) years. Over half of the respondents were not covered by any insurance scheme and 73% lived in urban areas. Mothers had a mean age of 37.3 (7.8), with one‐fourth being illiterate, while fathers had a mean age of 45.4 (9.3). Twenty per cent of parents had higher education. Two‐thirds of the participants had their HbA1C levels checked within the last 3 months. The prevalence of uncontrolled diabetes was 78.0%. No statistically significant association was found between HbA1C levels and families' socioeconomic, demographic or clinical characteristics (p > 0.05). Conclusion Neither children' nor parents' characteristics influenced HbA1C level. The high rate of uncontrolled diabetes (78.0%), and other countries showing better profiles of control, suggests the need for exploring other contributing factors. Insulin availability and lack of home glucose monitoring need to be considered. We recommend future prospective studies to consider these factors and use multiple HbA1C measures' average as a better indicator of diabetic control.